Mediated Time
XVII, 365 p. 9 illus., 2 illus. in color.
Keywords: Exploring mediated time, this book contemplates how far (and in what ways) media and time are intertwined from a diverse set of theoretical and empirical angles. It builds from theoretical discussions concerning the question of mediation and the normative framing of time (especially acceleration) and works its way through questions of time for/of one’s own, resisting temporalities, polychronicity, in-between-time, simultaneity and other time concepts. It further examines specific time frames, imaginations of a media future and the past, questions of online journalism and multitasking or liveness. Bringing together authors from diverse backgrounds, this collection presents a rich combination of milestone articles, new empirical research, enriching theoretical work and interviews with leading researchers to bridge sociology, media studies, and science and technology studies in one of the first book-length publications on the emerging field of media and time.